KAIZEN CONTINUOUS IMPROVEMENT - Yenque D., Julio (2002)
Many times we ask the question why Japanese companies are competitive?, Surely many of the answers to this mystery have support in the Kaizen. And the Kaizen is not a simple concept, it is a whole way of life that involves both managers and workers in the pursuit of progressive improvement of enterprises. In his book Kaizen, The Key to Japanese Competitive Advantage, Masaaki Imai explains in simple terms what is the essence of this philosophy: Kaizen means improvement means further progressive improvement that involves everyone and means that our way of life, and whether at work or in social and family life, is so valuable that it should be improved constantly.